Liquid metal enabled conformal electronics - Ping, Bingyi; Zhou, Guanxi; Zhang, Zihang; Guo, Rui (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional conformal electrons which can be directly applied to arbitrary surfaces have aroused people's interest, because of their applications in the fields of human health monitoring, intelligent robots and wearable electronic devices, especially for the realization of electronic devices on the dynamic three-dimensional interface of biology stable adhesion and high-quality signal acquisition has an important application prospect. In recent years, liquid metal (LM) materials have been widely used in the manufacture of flexible sensors and wearable electronic devices because of their excellent tensile properties and electrical conductivity at room temperature. In addition, LM has good biocompatibility and can be used in a variety of biomedical applications. Here, the recent development of LM flexible electronic printing methods for the fabrication of three-dimensional conformal electronic devices on the surface of human tissue is discussed. These printing methods attach LM to the deformable substrate in the form of bulk or micro-nano particles, so that electronic devices can adapt to the deformation of human tissue and other three-dimensional surfaces, and maintain stable electrical properties. Representative examples of applications such as self-healing devices, degradable devices, flexible hybrid electronic devices, variable stiffness devices and multi-layer large area circuits are reviewed. The current challenges and prospects for further development are also discussed.